2013
DOI: 10.1186/1471-2334-13-372
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of herpes zoster among hiv-positive patients in the german competence network for HIV/AIDS (KompNet): a cohort study analysis

Abstract: BackgroundHIV infection is a risk factor for the development of Herpes zoster (HZ) and its complications. Prior to antiretroviral therapy (ART), HZ incidence in HIV-infected individuals ranged from 2.9–5.1/100 person-years. There is limited evidence for the impact of ART on HZ occurrence among HIV-infected adults. We analysed the incidence of, and risk factors for, HZ in a large cohort of German HIV-positive patients.MethodsThe study population was taken from the German KompNet cohort, a nationwide multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
2
33
1
2
Order By: Relevance
“…In a recent study of HIV-infected patients conducted in Germany, the incidence of herpes zoster was 12/1000 person-years, while a cohort in the USA experienced herpes zoster at a rate of 9/1000 person-years. 11,12 These estimates are both substantially higher than the incidence rate in the general population of resource-rich countries, which ranges from 2/1000 person-years to approximately 5/1000 person-years. 10,13 …”
Section: Introductionmentioning
confidence: 90%
“…In a recent study of HIV-infected patients conducted in Germany, the incidence of herpes zoster was 12/1000 person-years, while a cohort in the USA experienced herpes zoster at a rate of 9/1000 person-years. 11,12 These estimates are both substantially higher than the incidence rate in the general population of resource-rich countries, which ranges from 2/1000 person-years to approximately 5/1000 person-years. 10,13 …”
Section: Introductionmentioning
confidence: 90%
“…26 In cohort studies conducted before the introduction of highly active antiretroviral therapy, incidence rates of 29.4-51.5 per 1000 person years had been reported among HIV-infected adults, reflecting 12-to 17-fold increase compared with HIV-negative persons. 1,12 More recent studies have detected lower incidence rates than previously (9.0-12.2 per 1000 person-years), 46,47 showing that appropriate antiretroviral therapy is an important protective factor for HZ. 47 The increased incidence of HZ in patients with hematological malignancies and solid tumors has been known for years, and both the nature of the underlying cancer and the type of treatment determine the magnitude of risk.…”
Section: Sociodemographic Factorsmentioning
confidence: 95%
“…1,12 More recent studies have detected lower incidence rates than previously (9.0-12.2 per 1000 person-years), 46,47 showing that appropriate antiretroviral therapy is an important protective factor for HZ. 47 The increased incidence of HZ in patients with hematological malignancies and solid tumors has been known for years, and both the nature of the underlying cancer and the type of treatment determine the magnitude of risk. 1,22 It has been demonstrated recently that, although HZ risk declined with time following a cancer diagnosis, it was still significant at least 5 y afterwards.…”
Section: Sociodemographic Factorsmentioning
confidence: 95%
“…Probably this finding is attributed to the comparably small group size (n = 95): Because we cover a cumulative observation period of only 56 person-years, our finding corresponds to an incidence of < 1.79 per 100 person-years, which is still in line with the literature reporting herpes zoster incidences of 0.9-1.7 per 100 person-years in the current antiretroviral therapy era. 26,27 Furthermore, we cannot exclude that a pronounced immunodeficiency in this group may blunt rises of anti-VZV IgG levels, in response to VZV reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…25 Besides age dependency, incidence increases with certain conditions that impair cell-mediated immunity, for example infection with human immunodeficiency virus (HIV), leading to an incidence of 2.9-5.1 per 100 person-years in HIV-infected patients, prior to the introduction of highly-active antiretroviral therapy; and 0.9-1.7 per 100 person-years in the current antiretroviral therapy era. 26,27 We performed statistical simulations, assuming a base-line incidence of herpes zoster in healthy people of 0.003 per person-year and a hypothetical 50% increase in herpes zoster incidence in MS patients treated with novel DMDs. These simulations indicated that 64,913 person-years of follow-up would be required per patient group to observe a relative risk (RR) of 1.5 at a global significance level of 0.05, with a power of 0.8.…”
Section: Introductionmentioning
confidence: 99%